Effects of inulin on protein in frozen dough during frozen storage. Issue 9 (17th August 2020) - Ke, Yuan; Wang, Yangyang; Ding, Wenping; Leng, Yue; Lv, Qingyun; Yang, Heng; Wang, Xuedong; Ding, Beibei
Abstract : Inulin exhibits a good protection effect on protein in frozen dough. Abstract : Effects of inulin on protein in frozen dough during frozen storage were investigated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). The strength of electrophoretic bands in A1 (32–57 kDa) and A2 (20–25 kDa) regions and the content of freezable water and sulfhydryl in frozen dough with inulin were lower than those of the blank under the same storage time. The gluten structure of frozen dough with 2.5 wt% long-chain inulin was more dense and compact than that of the sample with 5.0 wt% short-chain inulin after 2 weeks. Moreover, 4 weeks later, the change of the α-helix and β-sheet with 2.5 wt% long-chain inulin was lowest. These characteristics suggested that long-chain inulin exhibited a better protection effect on protein in frozen dough and showed a promising prospect for application in the food industry.